Use of Humor in Indian Advertisements: Can it help Mar Competition? - psgim, jcrm (Journal of Contemporary Research in Management (JCRM), 2023)
Humor is increasingly used as an effective mode in advertising for it is believed that it attracts consumers’ attention and helps occupy the mind space of consumers. . Humor aids in pushing across the message of the advertisements without exasperating the viewers. The fun aspect present in the advertisement makes it grab attention of the viewers at large. It enhances Brand easily perceptibility and remembrance of the brand may trigger purchase. According to recent estimates nearly one out of every five television ads comprises humor appeals. The use of humor is an important strategy for marketers. Research in this area suggests that humor is a widely acknowledged method of commercial appeal. When using humor as an advertising appeal it is imperative that it must be aligned with the nature of product, communication aims, channel of communication and the target segment of market. This article thus makes an attempt to analyze the Indian trend of this noteworthy advertising technique and discusses the concept, impact and its effectiveness on consumers. A limited amount of research has been done on the subject in India and the present work lends significant credence to the practice of using humor in advertisements and has implications for companies and consumers. It contributes to gaining insights for the use of humor as advertising device for gaining competitive advantage in the competitive market scenario.